2000
DOI: 10.1038/72777
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of a nuclear receptor gene, NR2E3, causes enhanced S cone syndrome, a disorder of retinal cell fate

Abstract: Hereditary human retinal degenerative diseases usually affect the mature photoreceptor topography by reducing the number of cells through apoptosis, resulting in loss of visual function. Only one inherited retinal disease, the enhanced S-cone syndrome (ESCS), manifests a gain in function of photoreceptors. ESCS is an autosomal recessive retinopathy in which patients have an increased sensitivity to blue light; perception of blue light is mediated by what is normally the least populous cone photoreceptor subtyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
386
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 428 publications
(407 citation statements)
references
References 24 publications
10
386
0
1
Order By: Relevance
“…However, a pathogenic homozygous mutation in the NR2E3 gene (c.290G>A, p.R97H) was identified (Supplementary Figure S1 online) that was reported to cause enhanced S cone syndrome (ESCS) in previous studies. 20,21 To explain this inconsistency, proband W29-1 was sent for a clinical reassessment. Full-field electroretinography showed extinguished rod responses (Supplementary Figure S1 online).…”
Section: Revision Of the Initial Clinical Diagnosismentioning
confidence: 99%
“…However, a pathogenic homozygous mutation in the NR2E3 gene (c.290G>A, p.R97H) was identified (Supplementary Figure S1 online) that was reported to cause enhanced S cone syndrome (ESCS) in previous studies. 20,21 To explain this inconsistency, proband W29-1 was sent for a clinical reassessment. Full-field electroretinography showed extinguished rod responses (Supplementary Figure S1 online).…”
Section: Revision Of the Initial Clinical Diagnosismentioning
confidence: 99%
“…Nr2e3 is expressed in retinal photoreceptor cells beginning around E18 in the mouse, peaking during rod differentiation and persisting into adulthood at a decreased level (Kobayashi et al, 1999;Takezawa et al, 2007). Expression appears primarily localized to the outer nuclear layer (Kobayashi et al, 1999;Haider et al, 2000;Haider et al, 2001). This persistent expression, mainly in rods in mammals (Bumsted O'Brien et al, 2004;Chen et al, 2005;, suggests that Nr2e3 plays a major role in rod differentiation and maintenance.…”
Section: Nr2e3 Is a Dual Transcription Regulator Required For Terminamentioning
confidence: 99%
“…Human genetic studies: Mutations in human NR2E3 cause enhanced S-cone syndrome (ESCS), an autosomal recessive disease featuring hyperfunction of blue cones, defective function of rods, and blindness in the late stages (Haider et al, 2000;Jacobson et al, 2004;Wright et al, 2004). Histopathological studies showed excess S-cones in the retina, some of which express both S-and M-cone opsins (Milam et al, 2002), which is unusual in humans (Lukats et al, 2005;Peichl, 2005).…”
Section: Nr2e3 Is a Dual Transcription Regulator Required For Terminamentioning
confidence: 99%
“…NR2E3 (a nuclear receptor) is required for normal photoreceptor development, and recent studies have demonstrated NR2E3 can interact with CRX and regulate transcription at Opsin promoters. (Cheng, et al, 2004, Haider, et al, 2000 Nuclear receptors, as a family, are noted for both repression and activation effects that are mediated through Znfinger proteins. (Belandia, et al, 2002) Recent studies also indicate that the interaction of NR2E3 with NRL or CRX may not be direct and additional transcriptional regulatory proteins might be necessary for the formation of a stable complex in vivo.…”
Section: Fiz1 Can Modulate Nrl and Crx-mediated Activation Of Rod Spementioning
confidence: 99%
“…(Akagi, et al, 2004, Brown, et al, 1998, Brown, et al, 2001, Hojo, et al, 2000, Kanekar, et al, 1997, Marquardt and Gruss, 2002, Moore, et al, 2002, Morrow, et al, 1999, Yan and Wang, 1998 Several transcription factors are clearly essential for photoreceptor development, and their mutations cause retinal degenerations: NRL, CRX, Otx2, Trβ2 (thyroid hormone receptor β2), and NR2E3. (Bessant, et al, 1999, DeAngelis, et al, 2002, Freund, et al, 1997, Haider, et al, 2000, Haider, et al, 2001, Martinez-Gimeno, et al, 2001, Ng, et al, 2001, Nishida, et al, 2003, Swain, et al, 1997 However, our knowledge of the interactions of these cell-specific proteins with each other and upstream signal transduction proteins remains sparse. We do not know how this pool of cell-specific transcription factors interacts with the pool of ubiquitous proteins, which include the general transcription machinery and epigenetic regulators of chromatin/DNA structure.…”
Section: Introductionmentioning
confidence: 99%